Clinical correlation between dry eye and pterygium: a study done at government medical college Jammu, Jammu and Kashmir, North India - Manhas, Angli; Gupta, Dinesh; Gupta, Aditi; Kumar, Dinesh; Manhas, Rameshwar S.; Manhas, Gaurav S. (International Journal of Research in Medical Sciences, 2017)
Background: To study the prevalence of dry eye among the patients of pterygium and to find the clinical correlation between dry eye and pterygium. Methods: The study was conducted at postgraduate department of Ophthalmology of GMC Jammu over a period of one year. 90 pterygium patients and 180 age and sex matched controls presenting to the eye OPD of GMC Jammu were included in the study. The TBUT, Schirmer’s test, basal tear secretion and Rose Bengal staining score were estimated in all patients. A TBUT of less than 10 seconds, a Schirmer’s test of less than 10mm, basal tear secretion of less than 10mm, Rose Bengal staining score of more than 3 were considered abnormal. Results: Redness 57 (63.33%) was the most frequently occurring symptom in pterygium patients followed by cosmosis 49 (54.44%). The mean TBUT, mean Schirmer’s, mean basal secretion and mean Rose Bengal staining score values were 9.88±3.39 seconds, 13.17±4.57mm, 10.11±4.81mm and 3.27±1.85 in pterygium patients and 14.22±3.99 seconds, 16.40±5.21mm, 12.19±5.05mm and 2.49±1.86 in the control group respectively. There was a statistically significant difference in the dry eye results between the pterygium patients and control groups (p<0.001). The odd’s ratio between dry eye and pterygium was 3.83, dry eye was present in 53 pterygium patients. Conclusions: The prevalence of dry eye in pterygium patients was 58.89% which suggests that there is a strong positive clinical correlation between dry eye and pterygium.